Surgical Models to Explore Acellular Liver Scaffold Transplantation: Step-by-Step. (2nd July 2020) - Dias, Marlon L.; Batista, Cíntia M. P.; Secomandi, Victor J. K.; Silva, Alexandre C.; Monteiro, Victoria R. S.; Faccioli, Lanuza A.; Goldenberg, Regina C. S.
ABSTRACT: Acellular liver scaffolds (ALS) have arisen as potential candidates for transplantation. Until now, all reports involving ALS transplantation failed in surgical method descriptions and do not offer support to scientists to reproduce the procedures used in experimental microsurgery to make the results comparable to literature. To overcome the lack of detail information, we described surgical steps details to perform heterotopic and partial orthotopic surgical models to promote ALS transplantation. After preservation and vessel cannulation steps, the liver grafts were decellularized. In addition, ex vivo blood perfusion tests were performed to obtain a successful anticoagulation treatment prior in vivo transplantation. Then, methods of partial liver resection, combination of hand-suture and cuff techniques to complete end-to-end anastomosis between the scaffold and the recipient animal were performed. These procedures which take 30–60 min and were efficient to allow acellular liver scaffold viability and recellularization of different types of cell post-surgery. In conclusion, our methods are practical and simple promising approach that provides the opportunity to investigate ways to achieve sufficient liver function post-transplantation in vivo .